EFFECT OF WORK FORM HOME AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN INDONESIA DURING THE COVID 19 PANDEMIC - Hertina, Dede; Manhayat, Tb Teddy Adha; Haris, Risda Herlianty (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this study was to determine the effect of working from home and work discipline on employee performance in Indonesia during the Covid 19 pandemic. This research method is qualitative with descriptive research type used to determine the introduction between variables. The data collection technique is by distributing questionnaires to 52 respondents. This study uses multiple regression analysis. The findings from this study are that the quality of working from home, work discipline, and employee performance in Indonesia during the Covid-19 pandemic are not significant. The results of the study simultaneously stated that work from home and work discipline on employee performance in Indonesia during the Covid 19 pandemic had a significant effect on employee performance in Indonesia during the Covid 19 pandemic. The results of the study partially that working from home has a negative and insignificant effect on employee performance and work discipline has a positive and significant effect on employee performance in Indonesia during the Covid 19 pandemic.